The effect of okra powder on blood glucose levels in women with gestational diabetes mellitus: A non-blinded randomized controlled trial - Mahla Salarfard; Zahra Abedian; Seyed Reza Mazlum; Hasan Rakhshandeh; Farideh Akhlaghi (Kashan University of Medical Sciences, 2023)
Background: Gestational Diabetes Mellitus (GDM) is one of the common medical complications during pregnancy, and a diet is the first line of treatment for it.Objectives: This study determined the effect of okra powder on the blood glucose levels of women with GDM who were on diet.Methods: This non-blinded randomized controlled trial was conducted on 60 women with GDM who were randomly allocated into two groups. The usual diet for gestational diabetes was taught to both groups. The intervention group also consumed 6 grams of okra skin and seed powder orally in a divided dosage twice daily for 4 weeks. Before, two and four weeks after the start of the study, fasting and 2-hour postprandial glucose (PPG) was measured. The data were analyzed by t-test, Mann-Whitney U test, Chi-square, and Friedman test.Results: The mean baseline fasting blood sugar (FBS) did not differ significantly between the women in the intervention and control groups (P=0.954). However, mean FBS was significantly lower in the intervention group at two weeks and four weeks after the baseline (P<0.001). The mean baseline 2-hour PPG did not significantly differ between women in the intervention and control groups (P=0.955). However, the mean 2-hour PPG was significantly lower in the intervention group at two weeks and four weeks after the baseline (P<0.001).Conclusion: The okra powder was effective in reducing FBS and 2-hour PPG in women with GDM who were on diet therapy.